2022
DOI: 10.1186/s12887-022-03434-8
|View full text |Cite
|
Sign up to set email alerts
|

“Struggle at night – He doesn’t let me sleep sometimes”: a qualitative analysis of sleeping habits and routines of Hispanic toddlers at risk for obesity

Abstract: Background Hispanic children face disproportionately higher risks for early life obesity and resultant comorbidities such as Type 2 diabetes and fatty liver disease. Sleep habits are modifiable behaviors that impact early childhood obesity; Hispanic infants have been shown to have less nighttime sleep compared to their white counterparts. Pediatricians often coach families on parents’ nighttime responsive feeding and longer child sleep duration as protective factors against early life obesity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Recent qualitative research provides additional context regarding sleep hygiene and home environment among Latino children. Gray, Vazquez and Agnihotri highlighted some of these factors [29 ▪▪ ] in a qualitative study among Latino mothers and their 6- to 18-month-old children. Authors found that while mothers desired to have their child sleep in a separate bed or room, they lacked the resources to do so.…”
Section: Current State Of Pediatric Sleep Research Among Latinosmentioning
confidence: 99%
“…Recent qualitative research provides additional context regarding sleep hygiene and home environment among Latino children. Gray, Vazquez and Agnihotri highlighted some of these factors [29 ▪▪ ] in a qualitative study among Latino mothers and their 6- to 18-month-old children. Authors found that while mothers desired to have their child sleep in a separate bed or room, they lacked the resources to do so.…”
Section: Current State Of Pediatric Sleep Research Among Latinosmentioning
confidence: 99%